Specific patterns of laryngeal electromyography during wakefulness are associated to sleep disordered breathing and nocturnal stridor in multiple system atrophy. (October 2016) - Alfonsi, E.; Terzaghi, M.; Cosentino, G.; Tassorelli, C.; Manni, R.; Pozzi, N.; De Icco, R.; Bertino, G.; Todisco, M.; Alvisi, E.; Fresia, M.; Pacchetti, C.; et al.
Abstract: Background: Nocturnal stridor and respiratory abnormalities are important features of multiple system atrophy (MSA) with relevance to patient survival, and they are detected and evaluated mainly through video-polysomnography (video-PSG). Diurnal laryngoscopy seems to yield abnormal findings only in the presence of significant vocal cord (VC) dysfunction. Aim: To assess whether specific electrophysiological patterns of diurnal EMG of VC muscles may indicate nocturnal stridor or respiratory dysfunctions in MSA patients. Materials and methods: Seventeen patients with probable MSA were examined. A full-night video-PSG to collect standard breathing parameters (apnea/hypopnea index, mean HbSAO2, oxygen desaturation index, total sleep time with HbSaO2 below 90%) was performed in all the patients. Laryngoscopy and EMG investigation of adductor (thyroarytenoid-TA) and abductor (posterior cricoarytenoid-PCA) muscles of the VCs were also performed. Results: Both the laryngeal EMG abnormalities (based on MUAP analysis and kinesiologic EMG investigation of VC muscles) and the laryngoscopic alterations correlated with video-PSG respiratory abnormalities. Specific patterns of EMG findings were consistently found in MSA subjects with nocturnal stridor detected at PSG. In particular, the following EMG findings were related to the severity of breathing abnormalities and the presence of stridor on video-PSG: neurogenic pattern on MUAP analysis of the PCA, paradoxical activation of the TA during inspiration and tonic EMG activity of the TA during quiet breathing. Conclusions: Electromyographic/kinesiologic investigation of VC muscles during wakefulness provides additional information on the pathophysiology of the respiratory abnormalities in MSA patients that could be useful for guiding the choice of the best appropriate treatment and care. Highlights: Diurnal EMG of vocal cords shows different abnormalities in MSA. Paradoxical adduction of the vocal cords is related to nocturnal stridor in MSA. Diurnal laryngeal EMG abnormalities herald sleep disordered breathing in MSA. Diurnal EMG of vocal cords could improve the clinical management of MSA patients.